Multi-omics analysis reveals the mechanism of selenite reduction by Rhodococcus qingshengii strain isolated from selenium-rich mine - An, Jianhui; Yi, Dandan; Wu, Jing’e; Deng, Guang’ai; Wang, Zhiyong; Peng, Mu (Frontiers in Microbiology, 2025)
Rhodococcus species are renowned for their metabolic diversity and environmental adaptability, yet their selenium metabolism remains insufficiently studied. In our previously work, we isolated a highly selenite-tolerant strain, Rhodococcus qingshengii PM1, from selenium-rich soils in Enshi, China. To reveal the reduction mechanism of sodium selenite, integrated transcriptomic and metabolomic analyses were conducted. Biochemical assays confirmed that Se exposure induced pronounced oxidative stress in strain PM1 and elicited strong induction of the antioxidant defenses. A total of 308 differential metabolites were detected, with bioactive compounds, organic acids, lipids, secondary metabolites and organoheterocyclic compounds. A total of 1,511 differentially expressed genes were identified. These changes were primarily associated with sulfite reductase complex genes (CysNDHIJ), Fe–S cluster biosynthesis genes (SufBCDSE), glutathione metabolism, lipid remodeling, redox metabolic pathways and antioxidant pathways, all contributing to the detoxification and reduction of selenite. Notably, metabolites such as prostaglandin D3 were upregulated, reflecting lipid signaling in response to selenium, while others including physangulide, enhydrin, and sebacic acid were downregulated, indicating a metabolic shift away from lipid biosynthesis and secondary metabolism. These findings elucidate the molecular mechanisms underlying microbial selenite detoxification and highlight R. qingshengii PM1 as a promising candidate for bioremediation of selenium-contaminated environments.